Growth and development and athletic performance - Cameron, N. (Kinesiologia Slovenica, 2014)
Children follow a predictable pattern of growth and development that varies in timing and magnitude but is constant in the achievement of developmental landmarks. This predictability allows athletic performance at any age to be statistically controlled for level of maturity and for future size associated athletic performance values to be estimated. The pattern of linear growth experienced by all children is characterised by rapid growth during infancy, relatively constant growth during childhood, and then accelerated growth during the adolescent growth spurt prior to reaching adult maturity and the cessation of growth in length. Whilst this is a universal pattern it demonstrates a considerable degree of sexual dimorphism generally favouring early growth and maturation in girls and delay in boys. That delay in boys accounts for an extended period of growth leading to greater adult size. The pattern of linear growth is also not common in all tissues. In particular, soft tissues that are associated with fine and gross motor skills and coordination, cognitive ability, strength, endurance, and other aspects of athletic performance follow patterns that may be associated with but are less predictable than growth in length. For example, increase in size of the central nervous system (brain and spinal cord) demonstrates rapid change during foetal and infant periods and relatively slow growth from mid-childhood onwards, and no adolescent growth spurt in size. However, neural networks continue to increase in complexity throughout childhood and adolescence. In addition, the growth of some tissues, e.g., skeletal muscle and adipose tissue, also demonstrate significant sexual dimorphism resulting in characteristic android and gynoid phenotypes in adulthood and significant differences in athletic ability. The development of athletic performance during childhood and adolescence will thus be strongly influenced not only by growth in size and increasing complexity of the nervous system but also by rates of maturational change and sexual dimorphism.